Addressing sustainable challenges in China: The contribution of off-site industrialisation. Issue 3 (11th November 2014) - Zhai, Xiaolin; Reed, Richard; Mills, Anthony
Abstract : Purpose: – The purpose of this paper is to present an innovative approach to addressing increasing sustainable challenges facing China's built environment which are linked to a diverse range of factors including rapid economic and population growth. The research context includes mass urbanisation in and the Chinese construction industry's attitude towards adopting sustainable construction processes. The focus is placed on examining current on-site construction practices in China which have historically remained largely unchanged; this includes a high reliance on cheap labour accompanied by a substantial material waste. An alternative approach is to increase the uptake of off-site production in China's residential construction industry, however no previous studies have investigated the potential advantages and barriers of this alternative approach. Design/methodology/approach: – In collaboration with an industry organisation a survey was completed by 110 construction professionals in China. The questionnaire referred to 21 individual factors relating to their perception about the current and potential future uptake of off-site production in construction processes in China. Findings: – The results confirmed the existing level of off-site production in China's urban residential construction industry was relatively low. At present the cast-in-situ method was considered by stakeholders as the most effective approach. The findings also confirmed the benefits of off-site production are not fully understood by the housing construction industry in China. It is argued this knowledge gap reduces the Chinese construction industry's motivation levels when seeking to embrace the off-site production approach and adopt improved sustainable construction practices. Originality/value: – This is an original study designed to address a gap in knowledge as there has been no previous research conducted into the use of off-site industrialised process in China. The results provide a valuable insight into the uptake of off-site production in the residential construction industry and will assist stakeholders and policymakers to increase the level of sustainability.